2020
DOI: 10.1111/os.12580
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Augmentative Plating and Exchange Nailing for the Treatment of Nonunion of Femoral Shaft Fracture after Intramedullary Nailing: A Meta‐analysis

Abstract: Objective The aim of this meta‐analysis was to systematically evaluate the efficacy of augmentative plating (AP) and exchange nailing (EN) in the treatment of nonunion of femoral shaft fracture. Methods For the present meta‐analysis, PubMed, EMBASE, and the Cochrane Library were searched to identify relevant articles up to April 2019. Two investigators independently evaluated the quality of original publications following the guidelines proposed by the Cochrane Handbook. Data were extracted from the studies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…A recent meta-analysis demonstrated that the femoral shaft nonunion healing rate was 98.7% (225/228) in the plate augmentation group and 78.9% (202/256) in the exchange nailing group, with respective mean union times of 9.0 months and 10.9 months. 20…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent meta-analysis demonstrated that the femoral shaft nonunion healing rate was 98.7% (225/228) in the plate augmentation group and 78.9% (202/256) in the exchange nailing group, with respective mean union times of 9.0 months and 10.9 months. 20…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis of five randomized controlled trials (256 patients) indicated a union rate of 78.9%. 20 Plate fixation is also a preferred treatment method. The success rate of plate augmentation with bone grafting in the treatment of nonunion is reportedly 100%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the amount and direction of the IFM is not easy to control 2,17,18 . In addition, the nonunion rate was 10% 19 , and the complication rate was 20.5% 20 . Most importantly, implants that can accurately provide the optimal elasticity for the healing of simple fractures will become mainstream in the future.…”
Section: Introductionmentioning
confidence: 99%